Disaggregated renewable energy consumption and environmental pollution nexus in G-7 countries. (May 2020) - Destek, Mehmet Akif; Aslan, Alper
Abstract: Although it is widely accepted that renewable energy consumption is vital for environmental sustainability, the environmental effectiveness of individual renewable energy types is often overlooked. Therefore, this paper examined the multivariate relationship between disaggregated renewable energy (hydroelectricity, wind, solar and biomass) consumption, economic growth and environmental pollution for the period from 1991 to 2014 in G-7 (The Group of Seven) countries. The study used both augmented mean group estimator and panel bootstrap causality method to consider the cross-sectional dependence and country specific heterogeneity across G-7 countries. Empirical findings indicate that increasing biomass energy consumption was efficient to reduce carbon emission in France, Germany, Japan and the United States; increasing hydroelectricity usage was efficient to reduce carbon emission in Italy and the United Kingdom; wind energy consumption reduced emission in Canada and solar energy usage was efficient on reducing emission in France and Italy for observed period. Moreover, in case of panel, it is found that increasing hydroelectricity, biomass and wind energy consumption reduced carbon emissions while the impact of solar energy consumption is statistically insignificant in G-7 countries. In addition, the hydroelectricity consumption was found the most efficient renewable energy source to reduce environmental pollution for the panel of G-7 countries. Highlights: Disaggregated renewable usage consumption and carbon emission nexus is investigated. Increasing hydroelectricity usage reduces emission in Italy, the UK and the US. Increasing wind energy usage reduces emission in all G-7 countries excluding Japan. The effect of solar energy consumption on emissions is statistically insignificant.